Síntese e propriedades fotofísicas de 2-(5-aril-4,5-diidro-1H-1-fenilpirazol-3-il) fenóis e sistemas pirazolil-triazólicos derivados - Santos, Gabriel da Costa (2021)
The present work describes the synthesis, structural study and evaluation of the photophysical properties of a series of eight 1,3,5-triaryl-substituted 2-pyrazolin derivatives, as well as their application in obtaining a novel series of 2-(1,5-aryl-1H-pyrazol-3-yl)-phenol-1H-1,2,3-triazoles, 3-aryl = 2-OH-C6H4 and 5-aryl = Ph, 1-Naphthyl, 4-Br-C6H4, 4-F-C6H4, 4-OCH3-C6H4, 4-NO2-C6H4, 4-(N(CH3)2)-C6H4. The structural and electronic properties were investigated by high resolution mass spectrometry (HRMS), 1H, 13C and 19F NMR and by single crystal X-ray diffraction. The proposed methodology started with the synthesis of 2-pyrazoline precursors, called 2-(1,5-aryl-1H-pyrazol-3-yl)-phenols (5), obtained from cyclocondensation [3 + 2] between phenylhydrazine 4 and α,β-insaturated ketones, where, in this work, chalcones (3) were used which were synthesized by employing ortho-hydroxyacetophenone (1) and substituted benzaldehydes (2), in yields of 40-78%. Subsequently, the 2-pyrazolin derivatives 5 were subjected to evaluation of their photophysical properties of absorption, emission, fluorescence quantum yield and Stokes shift evaluated and correlated to theoretical calculations (TD-DFT) for the verification of the ESIPT phenomenon. The UV-Vis absorption properties of the 2-pyrazoline derivatives were evaluated in DCM, MeCN, AcOEt, EtOH, and DMSO as solvents and showed a fluorescence shift to the polar aprotic solvents, emitting a band in the blue region when excited at the least energetic transition of each compound. Furthermore, the 2-pyrazoline derivatives showed similar absorption and emission properties in the solid state with the previously mentioned in-solution assays. With the theoretical TD-DFT (Density Functional Theory) calculations performed, it was possible to observe that all compounds showed electronic density throughout the pyrazoline ring. Noteworthy, that by the LUMO orbital analysis, only the derivatives 5c (4-NO2-C6H4) and 5f (1-Naphthyl) exhibited the electronic density located in the portion of the molecule where the substituents were. In sequence, the 2-pyrazoline compounds 5 were precursors for the synthesis of 1,5-aryl-3-(2-(prop-2-in-1-yloxy) phenyl)-4,5-dihydro-1H-pyrazole 7 using propargyl bromide (6) as O-alkylating agent in obtaining terminal alkynes, via SN2-type reactions, in yields of 41-71%. Finally, the synthesized propargyl ethers 7 were employed in regioselective 1,3-dipolar cycloaddition reactions catalyzed by copper salts (CuAAC - Click Chemistry) with benzyl azide (8) to obtain 1H-1,2,3-triazolyl-pyrazolin 1,3,5-triaryl-substituted systems (9) in yields of 30-51%, being represented by five synthetic specimens.